(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Functional safety is an important component of safety in general, has received increasing attention in the petroleum and chemical industry, railway and other industries which used a complicated process, in case of failure can cause major damage and loss of life. Electric engineering is also among these industries. But quantitative analysis shows that the equipment of power plants does not satisfy stringent requirements of functional safety.